Bevacizumab and gastrointestinal perforations: a review from the FDA Adverse Event Reporting System (FAERS) database. Issue 10 (9th September 2021) - Wichelmann, Thomas A.; Abdulmujeeb, Sufyan; Ehrenpreis, Eli D.
Summary: Background: Bevacizumab is used in the treatment of advanced malignancies and has a "black box" warning for gastrointestinal perforations. Despite this known side effect, there are no large descriptive series of patients who experience bevacizumab‐induced gastrointestinal perforations. Aim: To review and describe post‐market cases of bevacizumab‐induced gastrointestinal perforation reported by healthcare professionals to the United States Food and Drug Association Adverse Event Reporting System (FAERS) database. Methods: In total, 74 025 cases of bevacizumab‐induced adverse drug reaction were reported to FAERS from January 1 2004 to July 6 2021. We identified 2874 cases of bevacizumab‐induced gastrointestinal perforation. A total of 1375 cases were determined to contain complete patient demographic data after the removal of duplicates and were reviewed. Subgroup analysis was completed on gastro‐oesophageal perforations given the lack of prior data. Results: The average patient age was 61.9 ± 11.4 years. A total of 698 cases included descriptive locations of perforations with most occurring in the large intestine (385 cases, 55.2% of specifically described cases). Colorectal cancer was the most common indication for bevacizumab (691 cases, 50.3%) followed by ovarian cancer (197 cases, 14.3%) and non‐small cell lung cancer (182 cases, 13.2%). Death was reported in 554 patients (40.3% of cases). Sixty‐two cases of gastro‐oesophageal perforation were identified. Conclusions: This is the largest collective descriptive study of bevacizumab‐induced gastrointestinal perforations, and sheds light on this often fatal complication. We additionally identified and described a rare subgroup of patients experiencing bevacizumab‐induced gastro‐oesophageal perforation not previously described. Abstract : This figure demonstrates data acquisition, demographics, and results of the study. 1375 cases of bevacizumab‐induced gastrointestinal perforation were identified from the FDA Adverse Event Reporting System (FAERS) database and reviewed. The median age of perforations was 61.9 years, 36% occurred in the large intestine. Most cases occurred in patients undergoing treatment for colorectal cancer. Perforations resulted in a 40.3% mortality rate. Of additional note, a rare group of bevacizumab‐induced gastro‐oesophageal perforations were identified and described. Interestingly, this subgroup was predominantly male and had a lower frequency of mortality reported comparative to the collective cases of bevacizumab‐induced gastrointestinal perforations (29%).